Federal Firearms Act, 52 Stat. 1250-51 (1938) - (:unkn) unknown (General Publisher, 1938)
Prohibited any person who has been convicted of a “crime of violence or is a fug[a]tive from justice” from receiving “any firearm or ammunition” which has been shipped in interstate commerce.
--
Keywords: POSSESSION - DANGEROUS PERSONS